A Simplified Space Vector Pulse Width Modulation Method Including Over Modulation Operation for Five Level Cascaded H-bridge Inverter with FPGA Implementation - Bogimi Sirisha; P. Satish Kumar (Institute of Advanced Engineering and Science, 2017)
This paper presents simplified control strategy of Space Vector Pulse Width Modulation method including over modulation region with linear transfer characteristic for cascaded H-bridge inverters. Because of large number of switching states of the cascaded H- Bridge inverter, the over modulation operation is very complex. And also requires incorporation of both under modulation and over modulation algorithms. The proposed control method is effective in terms of selecting the optimal switching states with reduced computational complexity using simplified linear calculations which makes it easier for digital implementation. The performance of the proposed method is simulated and tested experimentally through Spartan 3A FPGA processor for five level Cascaded H-bridge Inverter. The simulation results and harmonic analysis of voltage and current at various modulation indexes as are presented which are in well agreement.